Overall survival in patients with platinum-sensitive recurrent serous ovarian cancer receiving olaparib maintenance monotherapy: an updated analysis from a randomised, placebo-controlled, double-blind, phase 2 trial. Issue 11 (November 2016) - Ledermann, Jonathan A; Harter, Philipp; Gourley, Charlie; Friedlander, Michael; Vergote, Ignace; Rustin, Gordon; Scott, Clare; Meier, Werner; Shapira-Frommer, Ronnie; Safra, Tamar; Matei, Daniela; Fielding, Anitra; et al.
Summary: Background: In patients with platinum-sensitive recurrent serous ovarian cancer, maintenance monotherapy with the PARP inhibitor olaparib significantly improves progression-free survival versus placebo. We assessed the effect of maintenance olaparib on overall survival in patients with platinum-sensitive recurrent serous ovarian cancer, including those with BRCA1 and BRCA2 mutations ( BRCA m). Methods: In this randomised, placebo-controlled, double-blind, phase 2 trial involving 82 sites across 16 countries, patients with platinum-sensitive recurrent serous ovarian cancer who had received two or more courses of platinum-based chemotherapy and had responded to their latest regimen were randomly assigned (1:1) using a computer-generated sequence to receive oral maintenance olaparib (as capsules; 400 mg twice a day) or a matching placebo by an interactive voice response system. Patients were stratified by ancestry, time to progression on penultimate platinum, and response to most recent platinum. Patients and investigators were masked to treatment assignment by the use of unique identifiers generated during randomisation. The primary endpoint of the trial was progression-free survival. In this updated analysis, we present data for overall survival, a secondary endpoint, from the third data analysis after more than 5 years' follow-up (intention-to-treat population). We did the updated overall survival analysis, described in this Article at 77% data maturity, using a two-sided α of 0·95%. As the study was not powered to assess overall survival, this analysis should be regarded as descriptive and the p values are nominal. We analysed randomly assigned patients for overall survival and all patients who received at least one dose of treatment for safety. This trial is ongoing and is registered with ClinicalTrials.gov, number NCT00753545 . Findings: Between Aug 28, 2008, and Feb 9, 2010, 265 patients were randomly assigned to olaparib (n=136) or placebo (n=129). 136 patients had deleterious BRCA m. The data cutoff for this analysis was Sept 30, 2015. An overall survival advantage was seen with maintenance olaparib versus placebo in all patients (hazard ratio [HR] 0·73 [95% CI 0·55–0·96]; nominal p=0·025, which did not meet the required threshold for statistical significance [p<0·0095]; median overall survival was 29·8 months [95% CI 26·9–35·7] for those treated with olaparib vs 27·8 months [24·9–33·7] for those treated with placebo), and in patients with BRCA m (HR 0·62 [95% CI 0·41–0·94] nominal p=0·025; 34·9 months [95% CI 29·2–54·6] vs 30·2 months [23·1–40·7]). The overall survival data in patients with BRCA wild-type were HR 0·83 (95% CI 0·55–1·24, nominal p=0·37; 24·5 months [19·8–35·0] for those treated with olaparib vs 26·6 months [23·1–32·5] for those treated with placebo). 11 (15%) of 74 patients with BRCA m received maintenance olaparib for 5 years or more. Overall, common grade 3 or worse adverse events in the olaparib and placebo groups were fatigue (11 [8%] of 136 patients vs four [3%] of 128) and anaemia (eight [6%] vs one [1%]). 30 (22%) of 136 patients in the olaparib group and 11 (9%) of 128 patients in the placebo group reported serious adverse events. In patients treated for 2 years or more, adverse events in the olaparib and placebo groups included low-grade nausea (24 [75%] of 32 patients vs two [40%] of five), fatigue (18 [56%] of 32 vs two [40%] of five), vomiting (12 [38%] of 32 vs zero), and anaemia (eight [25%] of 32 vs one [20%] of five); generally, events were initially reported during the first 2 years of treatment. Interpretation: Despite not reaching statistical significance, patients with BRCA -mutated platinum-sensitive recurrent serous ovarian cancer receiving olaparib maintenance monotherapy after platinum-based chemotherapy appeared to have longer overall survival, supporting the reported progression-free survival benefit. Clinically useful long-term exposure to olaparib was seen with no new safety signals. Taken together, these data support both the long-term clinical benefit and tolerability of maintenance olaparib in patients with BRCA -mutated platinum-sensitive recurrent serous ovarian cancer. Funding: AstraZeneca.